Analisis Produktivitas Penggunaan Alat Berat Excavator dan Dump Truck pada Proyek Pembangunan Jembatan Hutumuri Kecamatan Leitimur Selatan Kota Ambon: Analysis of the Productivity of the Use of Excavator and Dump Truck Heavy Equipment in the Hutumuri Bridge Construction Project in Leitimur Selatan District, Ambon City - Huliselan, Kevin Michael Boudewin; Metekohy, Selly; Marantika, Meyke (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The Hutumuri Bridge Construction Project in Leitimur Selatan District, Ambon City has a budget of 2,333,110,000.00 with a planned implementation time of 120 calendar days in 2022. In the Hutumuri Bridge Construction Project Package II, in its implementation there were problems that arose in the implementation of this project, namely a decrease in heavy equipment work productivity influenced by the condition of the equipment, weather and terrain, ineffective use of heavy equipment, where during excavation work, the heavy equipment used at the project location, namely the excavator, was damaged due to the terrain and weather, as a result the bolts on the heavy equipment rusted and broke. The purpose of this study was to determine the production capacity, determine the time needed, and obtain the rental costs for excavators and dump trucks for the Hutumuri Bridge Construction Project in Leitimur Selatan District, Ambon City. The data collection method used by the author in this study is the Observation Method, the author conducted a field survey on the Project that was the object of the study, to obtain primary data in the form of documentation photos, and secondary data in the form of heavy equipment specifications, work drawings, time schedules. Based on the results of the calculation of the Productivity of the Use of Excavator and Dump Truck Heavy Equipment on the Hutumuri Bridge Construction Project, South Leitimur District, Ambon City, the productivity value of the PC 200 excavator heavy equipment was 14.56 m3 / hour and the dump truck was 5.47 m3 / hour on the Hutumuri Bridge Construction Project, South Leitimur District, Ambon City, the total time required for the excavator heavy equipment was 2.51 m3 / hour and the dump truck was 6.68 m3 / hour, and the rental cost for the excavator heavy equipment was Rp. 126,257.00 / hour and the dump truck was Rp. 566,859.00 / hour.